Housing Market in Malaga: An Application of the Hedonic Methodology - Alejandro F. Garcia (European Regional Science Association (ERSA), 2006)
The analysis of the factors that determine the price of the second-hand house, by means of the use of the hedonic methodology, constitutes the central objective of this work. This study has been applied to the market of the house corresponding to the municipality of Malaga (Spain), of where a sample of 1996 transactions, made during 2003, has been selected.This information has been facilitated by a real estate agency. The obtained results have allowed to identify those characteristics of the houses that more affect their price and quantify this influence, valuing it in monetary terms. It has been stated that the contribution of some structural attributes (the floor area, the number of toilets, the presence of private garage or the luminosity of the house) and others of location (proximity to the sea or downtown, and location in a certain zone) affects the price of the house decisively.
Keywords: 330